PENGINTEGRASIAN PROGRAM JAMINAN SOSIAL KELUARGA TERHADAP MARAKNYA PENGAMEN ANAK-ANAK DI SIMPANG 4 CHARITAS KOTA PALEMBANG - Yuni Antika; Aulia Turrahmi; Suryani Damayanti (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
The phenomenon of increasing numbers of child street performers at the Charitas intersection in Palembang reflects social issues closely related to family poverty, low levels of education, and weak child protection. This study aims to analyze the root causes that drive children onto the streets and formulate family-based policy recommendations through the integration of social security. The method used is a descriptive qualitative approach with field observation techniques, interviews with five street children, and a documentation study of regulations and previous research. The results of the study show that family economic factors are the dominant cause, characterized by large family size, unstable income, limited access to education, and the potential for exploitation by adults. The resulting impacts include dropping out of school, loss of growth and development opportunities, and the perpetuation of intergenerational poverty. These findings indicate that the policies that have been implemented so far, such as raids and temporary guidance, have not addressed the root of the problem. The conclusion of this study emphasizes the importance of integrated and sustainable interventions through the strengthening of social security, family assistance, and the restoration of access to education. The main recommendation is the integration of assistance programs such as PKH, KIP, KIS, and social assistance to ensure that children return to school and families receive adequate economic support in an effort to break the cycle of poverty.